Влияние диэлектрического барьера на распределение электрического поля в высоковольтной композитной изоляции электрических машин - Беспрозванных, А.В.; Бойко, А.Н.; Рогинский, А.В. (Електротехніка і електромеханіка, 2018)
Представлены результаты распределения электрического поля в высоковольтной композитной изоляции на основе предложенной математической модели накопления поверхностного заряда на границе раздела подложка – барьер. В установившемся режиме напряженность электрического поля в диэлектрическом барьере может превышать среднее значение на 50 % в зависимости от электрофизических характеристик и толщины компонентов. Показано, что в области малых времен переходного процесса на характер распределения электрического поля влияют как относительная диэлектрическая проницаемость, так и толщина диэлектрического барьера. Экспериментальная проверка выполнена для пяти типоразмеров стеклослюдобумажной ленты по 5-ть макетов в каждой. Установлено, что композитная изоляция с повышенным содержанием слюдинитового барьера и стеклотканью меньшей толщины имеет на (8-16) % более высокие значения длительной электрической прочности. Представлені результати розподілу електричного поля в високовольтній композитній ізоляції на основі запропонованої математичної моделі накопичення поверхневого заряду на межі розділу підложка – бар'єр. В сталому режимі напруженість електричного поля в діелектричному бар’єрі може перевищувати середнє значення на 50 % в залежності від електрофізичних характеристик та товщини компонентів. Показано, що в області початку перехідного процесу на характер розподілу електричного поля впливають відносна діелектрична проникність та товщина діелектричного бар'єру. Експериментальна перевірка виконана для п'яти типорозмірів склослюдінітової стрічки по 5-ть макетів в кожній. Встановлено, що композитна ізоляція з підвищеним вмістом слюдинітового бар'єру і склотканиною меншої товщини має на (8-16) % вищі значення тривалої електричної міцності. Introduction. Modern high-voltage systems for composite insulation of electrical machines consist of tape glass mica paper materials (dry or pre-impregnated). The electrical characteristics of a multilayer composite insulation system are determined by both the fractional content of the individual components and their electrophysical properties. Purpose. The analysis of the influence of electrophysical characteristics and thickness (fraction) of the dielectric barrier on the distribution of the electric field in the composite highvoltage insulation of electrical machines. Methodology. Simulation of surface charge accumulation at the interface between the substrate and the dielectric barrier is based on the Maxwell–Wagner theory for interfacial polarization. Practical value. The influence of the electrophysical characteristics and thickness of the dielectric barrier on the distribution of the electric field has been established. In the steady state, the electric field strength in the dielectric barrier exceeds the average value by 50 %. In the region of small transition times (up to 1 s), the relative dielectric constant of the barrier has a significant effect on the distribution of the electric field. The use of a dielectric barrier with a higher dielectric constant and fractional content in comparison with the substrate leads to an increase in electric field strength by 5 % relative to the average value in composite insulation. Experimental studies of the long-term electrical strength of glass mica-belt ribbons in the cured (thermosetting) state are consistent with the simulation results. Composite insulation based on glass fiber mica tape with a high content of the mica barrier and fiberglass of smaller thickness has (8-16) % higher values of long-term electric strength.